The exercise of self defence to cause death: a legal analysis under the Malaysian Penal Code - Mohamad Yunus, Mohamad Ismail (Sweet & Maxwell Asia, 2016)
On December 7, 2015, Mohamad Zulkifli Ismail, 50, allegedly stabbed two men who were trying to rob him at his house in Kampung Labohan, in Kerteh, Terengganu, causing the death of one of the men. Upon the arrest of Zulkifli, he claimed the act was in self-defence. The case was investigated under s 302 of the Penal Code that constitutes murder. Had the killing exceeded the right of self-defence? Thus, the main objective of this article is to analyse and discuss the relevant issue as to what extent does the law allow a person to exercise his right of self-defence to cause death? Is there any defence available if the accused person exceeded the right of self-defence?